ZONATION STUDY AND DENSITY OF MANGROVE FOREST IN EAST MORO VILLAGE OF MORO DISTRICT OF KARIMUN REGENCY RIAU ISLANDS - Sri Ratna Hidayati; Sofyan H. Siregar; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study was held in June-July 2014 in the east Moro Village coast. The method used was a survey method, where the data was obtained directly from the field. Observations on mangrove vegetation was done through transect line method and sample plots. The results indicated that the zoning of mangrove in Moro was complete. The study showed the existence of mangrove vegetation types from 15 species and 10 families. Mangrove vegetation comprised of R. apiculata, R. mucronata, R. stylosa, Avicennia lanata, Bruguiera gymnorhiza, Ceriops tagal, C. decandra, Sonneratia alba, Xylocarpus granatum, Lumnitzera littorea, Scyphiphora hydrophyllacea, Pandanus tectorius, Nypa fruticans, Scaevola taccada and Acrostichum speciosum. Parameter that observed from each zone is the shape of mangrove forest substrat, mangrove vegetation types and trees community. The density and zonation at each station were divided into three zones: front zone, middle zone and the rear zone, starting from the outermost point of mangrove species growth to the point of transition between sea and land. It was found that the most dominant mangrove was Rhizophora apiculata.Keywords: Mangrove, Zonation, Rhizopora apiculata, Moro